Preliminary study: Introduction pest of long bean flowers in South Sulawesi. Issue 1 (March 2021) - Aminah, S N; Nasruddin, A; Abdullah, T; Fatahuddin,; Syatrawati,
Abstract: Long bean ( Vignaunguiculata ssp. sesquipedalis) family Leguminosaeas the famous vegetable in Asia, growth widely at lowland and highland including Indonesia. The purpose of research is to identify pest of long bean flowers in farmer field that reduce loss yield. The survey about presence of insect-pest incidence conducted at long bean field in Pakkabba village, north Galesong district, Gowa Regency, South Sulawesi (5°14'8''S, 119°24'1''E) in July 2019. Visual observation in long bean field was conducted diagonally in fivesampling points (used 10 long bean flowers from three plants per sampling point). The sample contained symptoms of long bean pest were collected, identified and recorded. The result show spotted pod borer Marucatestulalis Geyer (Lepidoptera: Crambidae) after mass rearing pest in laboratory. Based the survey, this is potential pest caused loss yield of long bean and need more working manage it.